Cuproptosis patterns and tumor microenvironment in endometrial cancer - Chen, Junfeng; Wang, Guocheng; Luo, Xiaomei; Zhang, Jing; Zhang, Yongli (Frontiers in Genetics, 2022)
Cuproptosis is the most recently discovered mode of cell death. It could affect the metabolism of cancer cells and surrounding infiltrating immune cells. In recent years, many studies have also shown that the tumor microenvironment (TME) plays a critical role in tumor growth and development. Mounting evidence suggests that Cuproptosis would bring unique insights into the development of pharmacological and nonpharmacological therapeutic techniques for cancer prevention and therapy. However, no study has been done on the combination of cuproptosis and TME in any cancer. Herein, we investigated the relationship between cuproptosis-related genes (CRGs), TME, and the prognosis of patients with Uterine Corpus Endometrial Carcinoma (UCEC). We identified three CRGs clusters based on 10 CRGs and three CRGs gene clusters based on 600 differentially expressed genes (DEGs) with significant prognostic differences. Following that, the CRGs score based on DEGs with significant prognostic differences was established to evaluate the prognosis and immunotherapeutic efficacy of UCEC patients. The CRGs score was shown to be useful in predicting clinical outcomes. Patients with a low CRGs score seemed to have a better prognosis, a better immunotherapeutic response, and a higher tumor mutation burden (TMB). In conclusion, our study explored the influence of cuproptosis patterns and TME on the prognosis of cancer patients, thereby improving their prognosis.